Myomectomy During Early Pregnancy - Sarsam, Samar D. (AL-Kindy College Medical Journal, 2008)
Myoma is a common benign uterine tumor; thereforeit is common in pregnancy. One in ten women willhave complications related to myoma in pregnancy.Few treatment options are available during pregnancy,conservative treatment with analgesia, reassurance andsupportive therapy is almost always adequate but incarefully selected patients, myomectomy has beenperformed successfully without jeopardizingpregnancy outcome. The usual indications for surgeryduring pregnancy include torsion of pedunculateduterine myoma and obstructed labor, surgicalintervention during pregnancy is occasionallynecessary in uncommon cases of intractable pain.19 years old lady presented with intractable lowerabdominal pain during pregnancy. Ultrasound showedfetus of 18 weeks gestation and ovarian cyst. The paindid not respond to rest and sedation, so emergencyexploration laparotomy was done; incarceratedintramural uterine myoma was the cause of the pain, itwas enucleated successfully through myomectomyand the pregnancy progressed normally